2015
DOI: 10.1097/ico.0000000000000600
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Intracorneal Ring Segment Implantation and Corneal Transepithelial Collagen Cross-Linking in Keratoconus

Abstract: Intracorneal ring segment implantation is an effective procedure for visual and refractive improvement in keratoconic eyes. The addition of TE-CXL to the procedure compensates for residual superficial irregularities, disrupts the progression of the disease, and provides greater improvements in spherical values. The process is simply a deep stretch with superficial lamellar stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 17 publications
0
31
0
1
Order By: Relevance
“…The cost of surgery should have been questioned also, as it is important issue in developing countries like Egypt. [10][11][12][13][14] Another limitation of the present study was a small sample size. To detect small differences, a huge sample size is required.…”
Section: Section: Ophthalmologymentioning
confidence: 99%
“…The cost of surgery should have been questioned also, as it is important issue in developing countries like Egypt. [10][11][12][13][14] Another limitation of the present study was a small sample size. To detect small differences, a huge sample size is required.…”
Section: Section: Ophthalmologymentioning
confidence: 99%
“…1). Removal of duplicates and use of the selection criteria reduced the number of articles reporting the evaluation of ICRS in keratoconus to 95 articles 8,1416,26…”
Section: Resultsmentioning
confidence: 99%
“…The degree of the channel was determined using nomograms of specific ICRS used or was a 360-degree15,16,26,32,34,36,39,96 tunnel for inserting the segments. Five ICRS were used: Keraring (Mediphacos, Belo Horizonte, Brazil) ( references 8, 16, 27, 28, 31, 32, 36, 41, 42, 47, 54, 55, 5861, 64, 66, 67, 69, 70, 77, 80, 88, 92, 93, 9799, 102, 103, 107, 110, 112, 116 ), Ferrara ring (Ferrara Ophthalmics, Belo Horizonte, Brazil) ( references 14, 30, 35, 43, 62, 63, 76, 78, 81, 82, 84, 85, 89, 91, 94, 101, 104 ), Intacs (Addition Technology, Inc., Des Plaines, IL) ( references 16, 26, 33, 37, 39, 40,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elsaftawy et al 16 assessed sequential manual Keraring implantation and transepithelial collagen cross-linking in adult keratoconus. They operated on 40 eyes that were divided into two groups with the first group having Keraring implantation only while the second group having Keraring implantation followed by TE-CXL after 1 month and concluded that Keraring implantation is an effective technique for keratoconus but that the addition of TE-CXL has the advantages of halting the progression of the disease and providing more improvements in spherical refraction.…”
Section: Discussionmentioning
confidence: 99%